STRATEGI PEMASARAN KEDAI KOPI “COFEE ET BIEN” KOTA METRO - LAMPUNG - Fitriani, Fitriani; Kurniawan, Angga; Walimah, Siti (Derivatif : Jurnal Manajemen, 2021)
Changes in lifestyle and the development of certain types of music also encourage the kind of coffee shop business to grow. The purpose of this study was to see whether the number or the proliferation of new coffee shops operating and providing varied offers and menus could cause sales at Cofee et Bien's shops to increase or decrease. This study uses the IFE matrix calculation, IE matrix, QSP matrix analysis and SWOT analysis. This type of research is a descriptive qualitative research. Coffee et bien has experienced stable sales for 6 consecutive months as well as analysis of the internal and external environment of the shop and the formulation of a business strategy that is always applied to Coffe et bien.Keywords: Marketing Strategic, SWOT, IE Matriks, QSP Matriks